Responses of native and invasive woody seedlings to combined competition and drought are species-specific. (20th October 2020) - Bueno, Andrea; Pritsch, Karin; Simon, Judy
Abstract: Woody species invasions are a major threat to native communities with intensified consequences during increased periods of summer drought as predicted for the future. Competition for growth-limiting nitrogen (N) between native and invasive tree species might represent a key mechanism underlying the invasion process, because soil water availability and N acquisition of plants are closely linked. To study whether the traits of invasive species provide an advantage over natives in Central Europe in the competition for N under drought, we conducted a greenhouse experiment. We analyzed the responses of three native (i.e., Fagus sylvatica L., Quercus robur L. and Pinus sylvestris L. ) and two invasive woody species (i.e., Prunus serotina Ehrh. and Robinia pseudoacacia L. ) to competition in terms of their organic and inorganic N acquisition, as well as allocation of N to N pools in the leaves and fine roots. In our study, competition resulted in reduced growth and changes in internal N pools in both native and invasive species mediated by the physiological characteristics of the target species, the competitor, as well as soil water supply. Nitrogen acquisition, however, was not affected by competition indicating that changes in growth and N pools were rather linked to the remobilization of stored N. Drought led to reduced N acquisition, growth and total soluble protein-N levels, while total soluble amino acid-N levels increased, most likely as osmoprotectants as an adaptation to the reduced water supply. Generally, the consequences of drought were enhanced with competition across all species. Comparing the invasive competitors, P. serotina was a greater threat to the native species than R. pseudoacacia . Furthermore, deciduous and coniferous native species affected the invasives differently, with the species-specific responses being mediated by soil water supply.